Investigation of Shear Wave Velocity by Using Multi-Channel Analysis of Surface Wave Method for Microzonation Map Development and Its Application to Industrial Frame Structures - Nazri, Fadzli Mohamed; Tan, Chee Ghuan; Abdul Rashid, M.T. (Springer Verlag, 2018)
The present study focuses on determining soil dynamic property, specifically the shear wave velocity at the top 30 m, to establish seismic microzonation maps and to evaluate the effect of soil flexibility on the frame structures of industrial building design in terms of drift. The model of industrial building steel frame was built on the basis of a 3D model using the SAP2000 software. The applications of spring stiffness for rigid footing spring constraints include average shear wave velocity to define the shallow foundation of the structure. The flexible- and fixed-base models were developed to evaluate the structural performance.